Blowoff hysteresis, flame morphology and the effect of plasma in a swirling flow. (7th August 2018) - Choe, Jinhoon; Sun, Wenting
Abstract: This study focuses on the effect of a nanosecond pulsed plasma on flame stabilization in a model gas turbine dump combustor with an annular swirling flow. Contrary to the common belief that the lean blowoff limit is a single value at a given condition a hysteresis phenomenon on blowoff was observed, therefore the lean blowoff limit is not uniquely defined. This hysteresis phenomenon depends on the initial value of the equivalence ratio at which the flame was ignited and the air flow rate. Different flame morphologies were also observed depending on the equivalence ratio and the region where the flame was stabilized. If a nanosecond pulsed plasma was applied at the combustor nozzle exit a stable inner shear layer flame was always observed. The flame morphology and stability presented no sensitivity to either flow rates or the equivalence ratio. With plasma activation, the lean blowoff limit was significantly extended and the hysteresis phenomenon disappeared. This indicates that the plasma provided an additional mechanism for flame stabilization. The effect of discharge voltage and repetition frequency on the lean blowoff limit was investigated accordingly. It was found that plasma activation increased NO x concentration and decreased CO concentration through emission analysis. Measurement of NO x using a gas analyzer at different discharge conditions was conducted to understand the dominant factor in NO x formation.